Relationship between Elementary Students’ Activity Patterns and the Occurrence of Refractive Disorder - Sitorus, Francisca Teratai Anindithya; Aldy, Fithria; Amra, Aryani Atiyatul; Nasution, Malayana Rahmita (Talenta Publisher, 2024)
Background: Refractive disorder is circumstance in which the eye fails to focus the light coming from an object onto the retina resulting in blurred shadows. One of the risk factors that cause or increase the progressivity of refractive disorder is environmental factors. Environmental factors are avoidable factors and are related to the social aspects of a child, such as a child's habitual patterns in carrying close range activities (reading, using a computer, playing video games, and watching television), and also outdoor activities. Objective: To examine the correlation between student activity patterns and the occurrence of refractive disorder. Methods: This study used an analytical method with a cross sectional design. The data used are primary data obtained directly through visus examination with the Snellen Chart and filling out questionnaires by elementary school students. Results: Based on the results of the Chi-square test, it was found that there was a significant relationship (p < 0,05) between the duration, distance and position of the body when reading books with the occurrence of refractive disorder. There was also a significant relationship (p < 0,05) between duration, distance and body position when using gadgets with the occurrence of refractive disorder. Conclusion: There is a significant relationship between the activity patterns of the students when reading books and when using gadgets with the occurrence of the refractive disorder. Latar Belakang: Kelainan refraksi adalah keadaan di mana mata gagal untuk memfokuskan cahaya yang berasal dari suatu objek ke retina sehingga dihasilkan bayangan yang kabur. Salah satu faktor yang berisiko menyebabkan maupun meningkatkan progresivitas kelainan refraksi adalah faktor lingkungan. Faktor lingkungan merupakan faktor yang dapat dihindari dan berkaitan dengan aspek sosial seorang anak, seperti pola kebiasaan seseorang dalam melakukan aktivitas jarak dekat (membaca, menggunakan komputer, bermain video games, dan menonton televisi), dan juga aktivitas di luar ruangan. Tujuan: Untuk mengetahui hubungan antara pola aktivitas siswa dengan terjadinya kelainan refraksi. Metode: Penelitian ini menggunakan metode analitik dengan desain cross sectional. Data yang digunakan adalah data primer yang diperoleh secara langsung melalui pemeriksaan visus dengan Snellen Chart serta pengisian kuesioner oleh siswa/i sekolah dasar. Hasil: Berdasarkan hasil uji Chi-square didapati adanya hubungan yang signifikan (p < 0,05) antara durasi, jarak dan posisi tubuh ketika membaca buku dengan terjadinya kelainan refraksi. Didapati juga adanya hubungan yang signifikan (p < 0,05) antara durasi, jarak dan posisi tubuh ketika menggunakan gawai dengan terjadinya kelainan refraksi. Kesimpulan: Terdapat hubungan yang signifikan antara pola aktivitas para siswa pada saat membaca buku ataupun pada saat menggunakan gawai dengan terjadinya kelainan refraksi.